Imbuhan-pe Pengaruh Strategi Pemasaran dan Kualitas Pelayanan Mahasiswa terhadap Kepuasan Mahasiswa dalam Menerapkan Tata Kelola di Perguruan Tinggi Swasta (PTS): Pemasaran Pendidikan - Sekartaji, Putri Nurul Sekartaji; Minto Yuwono (Journal of Entrepreneurship and Strategic Management, 2025)
This study aims to examine the influence of marketing strategies and service quality on student satisfaction in the context of implementing academic governance in Private Universities. Private Universities as an education service provider faces challenges in improving competitiveness and service quality, amidst high education costs and rapid growth of new university. This study uses a descriptive qualitative approach through a literature study of previous literature and research results. The results of the study indicate that marketing strategies that consider consumer behavior, market segmentation, and universities' brand image, as well as service quality including aspects of tangible, reliability, responsiveness, assurance, and empathy. They are play an important role in shaping the level of student satisfaction. In addition, the application of academic governance through open information flow and training programs for staff has also been shown to support improving the quality of educational performance. Therefore, activities between marketing strategies, service quality, and academic governance are very important to improve student satisfaction and university competition in sustainable.